Becoming Modern. Young Women and the Recontruction of Womanhood in the 1920s - Rosenbeck, Bente (Kvinder, Køn & Forskning, 2003)
Bente Rosenbeck anmelder "Becoming Modern. Young Women and the Recontruction of Womanhood in the 1920s" af Birgitte Søland.